Auditoría de Gestión a la Unidad Educativa del Milenio Bernardo Valdivieso de la ciudad de Loja, periodo 2022. - Seraquive Puchaicela, Cinthya Daniela (2024)
The present Curricular Integration Work called “Management Audit of the Milenio Bernardo Valdivieso Educational Institution in the city of Loja, period 2022”, was carried out to provide the authorities of the educational institution with an efficient and solid management structure that allows them to know the compliance planning throughout the academic year and, in turn, make decisions that promote the achievement of institutional objectives. To evaluate the fulfillment with the proposed objectives that were aimed at conducting a management audit, a visit was made to the facilities of the educational institution to meet the management staff and issue the proper certificates to start the management audit, questionnaires with questions were created to evaluate the internal control system, also management indicators were created to stablish the level of efficiency, effectiveness and economy of the institution, obtaining from all the above mentioned due evidence to justify the results that these had. Then, through the compilation and analysis of the obtained information, the appropriate narrative forms were designed containing the deficiencies found, detailing the comments, conclusions and recommendations for the improvement of the institutional compliance. Likewise, a final report was issued to the rector of the institution indicating that the internal control of the institution, presents deficiencies such as: lack of monitoring and performance evaluation processes for staff, lack of management indicators, lack of administrative staff, lack of an organization and functions manual, lack of supplies and materials in laboratories and medical department, lack of classification of reagents in laboratories, inadequate space for the medical department, non-compliance with the functions of servers and workers, so the report is made available to the rector of the institution, for making decisions that he deems necessary for the progress of the institution.